The Nonlinear Schrödinger–Airy equation in weighted Sobolev spaces. (October 2022) - Castro, A.J.; Jabbarkhanov, K.; Zhapsarbayeva, L.
Abstract: We study the persistence property of the solution for the nonlinear Schrödinger–Airy equation with initial data in the weighted Sobolev space H 1 / 4 ( R ) ∩ L 2 ( | x | 2 m d x ), 0 < m ≤ 1 / 8, via the contraction principle.